First Australian Photogrammetric Conference, 7-9 November, 1991, University of New South Wales, Sydney, Australia: conference papers - Australian Photogrammetric Conference (1st : 1991 : Sydney, Australia); Australian Photogrammetric and Remote Sensing Society ([N.l.] : APRSS, 1991)
29